2004
DOI: 10.1242/jeb.00844
|View full text |Cite
|
Sign up to set email alerts
|

Seawater acclimation causes independent alterations in Na+/K+- and H+-ATPase activity in isolated mitochondria-rich cell subtypes of the rainbow trout gill

Abstract: SUMMARYMitochondria-rich cells (MR cells) of the gills of rainbow trout undergo changes in relative distribution and biochemical function during acclimation to partial-strength (10‰) and full-strength (30‰) seawater. In isolated total gill cells, Na+/K+-ATPase activity increased fivefold and H+-ATPase activity decreased fourfold when trout were acclimated to either 10‰ or 30‰ seawater. When total MR gill cells were separated based on differential binding to peanut lectin agglutinin (PNA), the PNA subtypes unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…As Cd causes a drop in the activity of basolateral NKA, lower quantities of Na + are removed from the MRC. Thus, the intracellular milieu becomes less electronegative, with a higher concentration of Na + , which impairs the entry of this ion through its channel in the apical membrane (Lin and Randall, 1991;Hawkings et al, 2004). The increase in gill HATPase activity in P. lineatus enhances cellular electronegativity and favors absorption of Na + .…”
Section: Discussionmentioning
confidence: 99%
“…As Cd causes a drop in the activity of basolateral NKA, lower quantities of Na + are removed from the MRC. Thus, the intracellular milieu becomes less electronegative, with a higher concentration of Na + , which impairs the entry of this ion through its channel in the apical membrane (Lin and Randall, 1991;Hawkings et al, 2004). The increase in gill HATPase activity in P. lineatus enhances cellular electronegativity and favors absorption of Na + .…”
Section: Discussionmentioning
confidence: 99%
“…As marine fish express H + -ATPase in their gills (mainly for acid secretion) (Evans et al, 2005), basal levels of this protein found in seawateracclimated Atlantic salmon gill may be sufficient to drive Na + uptake following freshwater exposure. As individual gill cell types are known to vary in their H + -ATPase activity (Hawkings et al, 2004), it is possible that measuring activity in whole gill homogenates may have masked significant increases in individual cell types responsible for the bulk of sodium flux (i.e. PNA -mitochondria rich cells).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also shown that changes in gill H + -ATPase appear to occur quite slowly in response to salinity change in salmonids. For example, Wilson and colleagues (Wilson et al, 2002) saw no change in H + -ATPase activity after 8days of seawater acclimation, while Hawkings and colleagues (Hawkings et al, 2004) and Lin and Randall (Lin and Randall, 1993) found decreased activity in rainbow trout sampled after 2weeks and 8-10weeks of seawater exposure, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Recently described PNA-positive MRCs that were distinguished from other MRCs by their ability to bind peanutlectin agglutinin (PNA) and called ␤ cells (Goss et al, 2001;Hawkings et al, 2004), fit the description of ␣ cells defined by Pisam et al (Pisam et al, 1987). It is still not clear whether ␣ and ␤ cells represent different subtypes of the MRC or different developmental stages in the life cycle of these cells (Wendelaar Bonga and van der Meij, 1989;Perry, 1997).…”
Section: +mentioning
confidence: 99%